1977
DOI: 10.1128/jvi.24.1.177-193.1977
|View full text |Cite
|
Sign up to set email alerts
|

Role of the T5 gene D15 nuclease in the generation of nicked bacteriophage T5 DNA

Abstract: The processing of newly replicated concatameric T5 DNA into both single stranded DNA chains of unit length and single-stranded fragments of sizes comparable to those found in mature T5 virion DNA occurs in the absence of late T5 protein synthesis. The formation of unit-length, single-stranded DNA chains does not require the early T5 gene D15 nuclease; however, the subsequent formation of the single-stranded fragments does require that the D15 nuclease be functional. A reexamination of the properties of the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Analysis of this structure for the open reading frame showed that the major one is found only in the r-strand of DNA and corresponds to the protein consisting of 291 amino acid residues (33.4 kDa). This agrees well with 35 kDa reported by Moyer and Rothe [2] after the partial purification of 5 ' -exonuclease. The Shine-D~garno sequence AGGA is tocated 12 nucleotides upstream from the initiation codon ATG.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Analysis of this structure for the open reading frame showed that the major one is found only in the r-strand of DNA and corresponds to the protein consisting of 291 amino acid residues (33.4 kDa). This agrees well with 35 kDa reported by Moyer and Rothe [2] after the partial purification of 5 ' -exonuclease. The Shine-D~garno sequence AGGA is tocated 12 nucleotides upstream from the initiation codon ATG.…”
Section: Resultssupporting
confidence: 92%
“…of Escherichiu cofi by bacteriophage T5, the gene DlS-encoded nuclease is produced which belongs to early proteins [l]. Enzymatic studies of purified D15 nuclease showed that the enzyme possesses 5 ' -+ 3 ' exonuclease activity on both single-and doublestranded DNA and can function (in vitro) also as a T5 DNA specific endonuclease [2]. This product performs 2 functions essential for the phage T5 life cycle: it is necessary for T5 DNA replication [3] and initiation of late transcription [4].…”
Section: During Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene D15 nuclease of T5 was originally described as a 5' --3' exonuclease (9), but subsequent examination showed that it also possessed an endonuclease activity specific for single-strand sites in duplex T5 DNA (23). However, there are also some distinct differences between the T5 and HSV nucleases.…”
Section: Resultsmentioning
confidence: 99%
“…Of approximately 150 survivors of hydroxylamine treatment that were screened in this manner, 16 were found to contain at least one mutation which caused an interruption-deficient 5 10 15…”
Section: Resultsmentioning
confidence: 99%